Assessing Supply Chain Management Performance with Independence and Responsibility of Internal Auditor to Adapt to Effective Audit Mechanisms - Ali Abdul-Hussein Raji; Dheyaa Zamil Khudhair; Firas. khudair Abbas Al-Zubaidi (International Journal of Supply Chain Management, 2019)
The work performed by audit teams within different organizations has been improving over the years. Internal auditors are part of the central role in the process of providing assurance and preventing fraud within an organization. Additionally, independent internal audit personnel have the responsibility of ensuring that there is a proper audit practice that is found in the firm. This paper seeks to develop a balanced assessment approach to assess the performance of supply chain management which evaluates daily business operations in four areas: financial perspective (or shareholders), learning and growth, customers and in-company business processes. The appreciation of the duties that are performed by the internal audit teams are mainly due to the major function that they play, especially in initiating an enabling environment or financial and economic organizational support. The study sought to carry out an in-depth discussion on the independence and the overall burden of internal auditors that is related to the promotion of effective audit practices and mechanisms. Additionally, the researcher will carry out interviews to ascertain the independence of internal auditors and examine their role in promoting effective internal audit mechanisms. The researcher will carry out the research using very specific mode of statistical analysis. The researcher will carry out the analysis of the hypothesis in the analysis using the Chi-Square technique and the application of SPSS as a major statistical tool.